A clarification for the subgenera of Paramacrobiotus Guidetti, Schill, Bertolani, Dandekar and Wolf, 2009, with respect to the International Code of Zoological Nomenclature - Marley, N.j.; Kaczmarek, Ł.; Gawlak, M.; Bartels, P.j.; Nelson, D.r.; Roszkowska, M.; D., Stec; Degma, P. (Zootaxa, 2018)
The recent re-description of Paramacrobiotus Guidetti, Schill, Bertolani, Dandekar and Wolf, 2009 has inadvertently led to the description of an objective synonym within its subgenera nominal taxa. To resolve this issue, we have re-described both subgenera, and proposed a new substitute name for one subgenus, in line with the International Code of Zoological Nomenclature. Additionally we have confirmed the placement of two recently published Paramacrobiotus species, not included in the last revision, within the respective subgenera established herein.